2014 9th International Conference on Computer Engineering &Amp; Systems (ICCES) 2014
DOI: 10.1109/icces.2014.7030977
|View full text |Cite
|
Sign up to set email alerts
|

ICPMD: Integrated cross-platform mobile development solution

Abstract: In these days, smartphones become much more used than the personal computers because of the various categories of applications downloadable from the store. The vendors of smartphones support different platforms hence to reach as many users as possible, the developer has to develop the same application for all these platforms using the different tools and programming languages provided by each platform vendor. Therefore the cross-platform mobile applications development solutions were introduced to develop the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For instance, PhoneGap allows users to create "hybrid applications built with HTML, CSS, and JavaScript" [1]; React Native enables the creation of apps "using only JavaScript" with "the same fundamental UI building blocks as regular iOS and Android apps" [10]; and XMLVM can "cross-compile" an Android application so that it will run on iOS [33]. Similarly, the academic literature includes several studies that propose the creation of development tools using new domain-specific languages, such as md2 [16], ScaMo [22], Xmob [11], ICPMD [8], and the Common framework [29,30].…”
Section: Related Work 21 Cross-platform Development Toolsmentioning
confidence: 99%
“…For instance, PhoneGap allows users to create "hybrid applications built with HTML, CSS, and JavaScript" [1]; React Native enables the creation of apps "using only JavaScript" with "the same fundamental UI building blocks as regular iOS and Android apps" [10]; and XMLVM can "cross-compile" an Android application so that it will run on iOS [33]. Similarly, the academic literature includes several studies that propose the creation of development tools using new domain-specific languages, such as md2 [16], ScaMo [22], Xmob [11], ICPMD [8], and the Common framework [29,30].…”
Section: Related Work 21 Cross-platform Development Toolsmentioning
confidence: 99%
“…We found relevant studies that provided an overview for the existing development tools (e.g., (Latif et al, 2017), (Ribeiro et al, 2012) and others). Further, we found some studies that reported the challenges in this field such as (Alamri and Mustafa, 2014); (El-Kassas et al, 2014). This motivated us to apply a rigorous systematic mapping study in order to provide a wide overview for the existing and most recent research in this emergent field.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…The study by (El-Kassas et al, 2014) [S23] aimed to provide an overview for the available cross-platform approaches. They described each approach in details, which are, Cross-Compilation, Virtual Machine, Model-Driven Development, Web-Based, Component-Based, Cloud-Based and Merged approach.…”
Section: Framework Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such approaches include Component-Based development (e.g. [32,74]) and Integrated Cross-Platform Mobile Development [28], the latter a proposed approach drawing from best practices inherited from other approaches. However, regardless of their novelty or possible application, we have yet to identify studies and experiments including these approaches, with the exception of those previously cited.…”
Section: Development Approaches and Domain Terminologymentioning
confidence: 99%